A Critical Analysis of the Qur’anic Concept of Qaw’am: In the Light of āl Riǧālū qawāmwn ʿla ālnisāʾ - Muhammad Sarwar; Dr. Muhammad Usman Khalid (jihat-ul-islam, 2022)
Allah Almighty has human being Adam and Eve, which is the basic Unit of the Society. Elucidatory, the basic unit of human society is based on the relation man and woman as an husband and wife. If their relationship is built on mutual understanding and take care of each other, then the whole society will be the cradle of peace, harmony and Prosperity. On contrary, if there remain flaws of misunderstanding, insecurity, then stability and prosperity of the society might be unachievable dream. So, the Holy Qur’an has declared men in charge of women by [right of] what Allah has given one over the other and what they spend [for maintenance] from their wealth. Here, the Holy Quran has described two reasons of men superiority and managing authority due to the will of Allah and the second one is because men spends their wealth for women. Interestingly, Majority of Islamic Theologians and Commentators of the Holy Qur’an are of the view that the main reason of men superiority is the will of Allah Almighty while Javed Ahmad Ghamdi is of the view that men superiority is due to spending wealth for women. If a man is unable to spend his wealth and a woman manage the expenses of family, then she will be Qawwam (superior). In the Article, the opinions of the Qur’anic experts will be critically analyzed.